The impact of traditional gold mining on land use changes and vegetation index in Mandor Subwatershed, West Kalimantan - Lisa Astridni Putri; Aji Ali Akbar; Romiyanto Romiyanto (Brawijaya University, 2023)
Traditional gold mining activities altered the environmental structure of the Mandor Subwatershed significantly. The expansion of critical land in the Mandor Subwatershed causes flooding due to the lack of water catchment areas. The purpose of this study was to identify the impact of traditional gold mining on land use change in the Mandor Subwatershed. The research was conducted with a spatial analysis approach using Landsat multitemporal images from 2002, 2013, and 2022, followed by a field survey. A comparison of the Normalized Difference Vegetation Index (NDVI) and the Enhanced Vegetation Index (EVI) methods was used to determine the changing process of vegetation density. The accuracy of vegetation index analysis indicated that the EVI method was more accurate for identifying vegetation density than the NDVI method. Land use change from 2002 to 2022 was dominated by an increase in the land area devoted to mining and oil palm plantations. The impact of this traditional gold mining has led to significant deforestation and land degradation over the past 20 years in the Mandor Subwatershed. This affects the condition of the surrounding environment as well as human health.